A study on the design and concept of Guilin Landscape Building in Shang Kuo based on the Beaux-Arts system - Pan Shen; Guangsi Lin (Journal of Asian Architecture and Building Engineering)
The Beaux-Arts system, once an important international architectural design method, represents a significant and challenging area of research when considering its localization in China. Shang Kuo, a Chinese architect influenced by the Beaux-Arts concept, demonstrates the heritage and development of the Beaux-Arts system through his landscape buildings in Guilin. This study selects six representative cases from Shang Kuo’s landscape buildings in Guilin and analyzes them based on the Beaux-Arts system. The analysis focuses on four aspects: plan composition, spatial composition, facade composition, and the formal aesthetic laws of composition. The research reveals that Shang Kuo’s works exhibit three balanced choices of axis composition in their plans. He innovatively incorporates elements such as residential buildings, garden architecture, traditional Chinese art, and natural elements into the composition of his buildings, while emphasizing the harmonious integration of interiors and facades and adhering to the principles of aesthetic form. This study shows the way of localizing Beaux-Arts architecture through Shang Kuo’s landscape buildings in Guilin and contributes to the understanding of the development of modern Chinese architecture.